Potential Effectiveness of Secondary Metabolites of Azolla microphylla as Aedes aegypti Repellent Guide - Pradana, Muhammad Sungging; Ekawati, Evy Ratnasari; Yusmiati, Siti Nur Husnul; Rosady, Imron; Cahyani, Ridanti Nagita (Transpublika Publisher, 2026)
Dengue Hemorrhagic Fever (DHF) remains an endemic public health concern, with Aedes aegypti mosquitoes serving as the primary transmission vector. While chemical repellents are widely used for vector control, their health and environmental risks have driven the need for safer, biodegradable natural alternatives. This study aimed to identify the secondary metabolite content of Azolla microphylla leaf extract and evaluate its effectiveness as a repellent against Aedes aegypti. This experimental study employed a post-test only control group design. Three extract concentrations (10%, 15%, and 20%) were tested alongside positive and negative controls, using 10 mosquitoes per group. Observations were conducted at 1, 2, 4, and 6 hours, with data analyzed using statistical tests to assess differences between treatment groups. Phytochemical screening confirmed the presence of flavonoids, terpenoids, and tannins in the extract. Repellent testing revealed that the 20% concentration provided the highest effectiveness, with an average mosquito repellency of 58% during the first 1–2 hours. However, effectiveness declined progressively across all concentrations over time. Statistical analysis confirmed a significant difference between treatment and control groups after 1 hour of observation (p < 0.05). Azolla microphylla leaf extract demonstrates potential as a natural repellent against Aedes aegypti; however, its protective effect is temporary due to the volatility of its active compounds. Further formulation development, such as encapsulation or the use of fixative agents, is needed to enhance the stability and durability of its repellent activity.